Evaluation of the reliability on WC-40%Co composites through Weibull analysis. (2020) - Kanagarajan, D.; Sivaraj, P.; Seeman, M.; Seetharaman, R.
Abstract: Tungsten carbide/Cobalt (WC–Co) composite is one of the important composite materials, which is used for manufacturing of cutting tools, dies and other special materials for high temperature application areas. It has superior hardness and high resistance to shock and wear. Conventional machining techniques are not suitable for machining of this material. Due to the excellent electrical and thermal conductivity of WC–Co, it is usually machined by Electrical Discharge Machining (EDM). EDM process of WC-Co composites often results in the damage of the machined surface would affect the reliability. It is important to investigate the effect of EDM process on the properties of WC–Co composites before applying its engineering application. For these composites, it is very important for maintenance of proper fracture strength and is to be controlled. In this work, an attempt has been made to investigate the material removal rate (MRR), the factors influencing MRR, the surface defects induced by EDM, fracture strength and the reliability of EDMed WC-Co composite using the Weibull distribution analysis. The comparison of results between the machined and un-machined composites is carried out and presented in this study.